2010
DOI: 10.1149/1.3490424
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Hexagonal Order: Formation of Self-Organized Anodic Oxide Nanotubes and Nanopores on a Ti–35Ta Alloy

Abstract: In this work, we report on the formation of highly aligned nanoporous or nanotubular oxide structures by anodization of Ti-Ta alloys in NH 4 F containing ethylene glycol electrolytes. We show that depending on the anodization conditions, either a hexagonally self-organized nanoporous layer or a nanotube array can be formed. Critical factors that decide on tube or pore formation are the water content of the electrolyte and the applied voltage. The present approach provides hexagonally packed oxide structures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…In this context, it is noteworthy that similar transition phenomena were reported on other valve metal alloys [36,124,161,162] and also on pure valve metals, such as zirconium and hafnium. [163][164][165][166] In each case it was found that a key parameter affecting the morphology is the concentration of H 2 O in the electrolyte.…”
Section: Transition From Porous To Tubular Structuressupporting
confidence: 79%
“…In this context, it is noteworthy that similar transition phenomena were reported on other valve metal alloys [36,124,161,162] and also on pure valve metals, such as zirconium and hafnium. [163][164][165][166] In each case it was found that a key parameter affecting the morphology is the concentration of H 2 O in the electrolyte.…”
Section: Transition From Porous To Tubular Structuressupporting
confidence: 79%
“…[29,[39][40][41] Self-ordered oxide nanotubes cannot only be grown on pure Ti, but also on other transition metals such as Mo, W, Ta, Nb, and so forth, and a full range of Ti alloys including TiW, TiNb, TiAl, TiMo, TiTa. [30][31][32][33][34] In the present work, we demonstrate a very strong effect of tungsten addition to the TiO 2 nanotubes in terms of their photocatalytic activity. For this, different TiW alloys (Ti 0.2 at % W (Ti 0.2 W) and Ti 9 at %W (Ti 9 W)) as well as pure Ti were anodized to form % 2 mm-long self-organized tube layers as shown in Figure 1.…”
supporting
confidence: 54%
“…[152] Under specific conditions, self-ordering at two length scales can be obtained. [153][154][155][156] The formation of these self-ordered structures in fluoride-containing electrolytes is not limited to Ti, but was also successfully demonstrated for other transition metals, such as Zr, [157][158][159][160] Hf, [161,162] W, [163,164] Nb, [165,166] and Ta, [167,168] and a full range of alloys, such as TiNb, [169] TiTa, [168,170] TiZr, [103,171] TiW, [172] TiMo, [173] and TiAl. [174] Recent reviews on the growth of these different systems are available.…”
Section: Specific Aspects Of Anodic Tio 2 Nanotubesmentioning
confidence: 91%